Pengaruh Mengunyah Permen Karet Gula Alkohol (Xylitol) Terhadap Volume Sekresi Saliva Pasien Gagal Ginjal Kronik Stadium V Di Ruang Hemodialisa RSUP Sanglah Denpasar. - Wira Pramana (Coping: Community of Publishing in Nursing, 2014)
Hyposalivation often occurs in patients with stage V chronic renal failure with complaints of dry mouth or xerostomia due to uremia syndrome. This research aimed to investigate the effect of chewing gum sugar alcohols (xylitol) on salivary secretion volume of patients with stage V chronic renal failure. This study is Pre-ekspremental with One-group pre-post test design. Sample consisted of 34 people (without control group) obtained from consecutive sampling. Saliva volume data collection using spitting method. The results showed that the difference of mean increase in salivary secretion volume before and after chewing gum. Before treatment the mean volume of 0.35 mL of saliva secretion, and the mean volume of salivary secretion after treatment was 0.65 mL. The result of Dependent “t” test statistical test yielded the value p<? (0,000<0,05), in which there was differences in secretion of saliva before and after chewing gum sugar alcohols (xylitol). Salivary secretion showed increased after chewing gum at 0.4 to 0.9 mL/min, in which it can be concluded that there had been a significant effect of chewing gum sugar alcohol (xylitol) for volume secretion of saliva patients with chronic renal failure stage V in haemodialysis unit of Sanglah General Hospital in Denpasar. Based on these results, it is expected that health workers - especially those working at the haemodialysis unit of Sanglah General Hospital – will plan alternative interventions in the form of chewing gum sugar alcohol (xylitol) therapy to increase the volume of secretion saliva on patients with chronic renal failure stage V.